Enhancing School Safety Through Evidence-Based First Aid Training: Strengthening Emergency Preparedness Among Physical Education Teachers - Ahmad Al Munawar; Afwa Raufi; Pedomanta Keliat; Sefterlima Harefa; Dira Khalisya (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This community service program aimed to enhance the knowledge, practical competencies, and emergency preparedness of Physical Education, Sports, and Health (PJOK) teachers who are members of the MGMP in Karo Regency in providing appropriate first aid during sports-related accidents and supporting safer physical education learning environments. Materials and methods: The program employed a Participatory Action Research (PAR) approach involving 20 PJOK teachers. The implementation consisted of a needs assessment through Focus Group Discussions (FGDs), interactive workshops, and hands-on simulation-based training covering first aid procedures, cardiopulmonary resuscitation (CPR), immobilization techniques, victim evacuation, and the evidence-based RICE, PEACE, and LOVE protocols. Program effectiveness was evaluated using pre-test and post-test questionnaires, performance observation sheets, and descriptive quantitative and qualitative analyses. Results: The training significantly improved participants' knowledge and practical competencies across all evaluated indicators. The average competency improvement reached approximately 95.1%, with notable gains in injury management using the RICE, PEACE, and LOVE protocols, CPR implementation, and emergency evacuation procedures. In addition to technical skill enhancement, participants demonstrated a positive shift toward evidence-based first aid practices and greater awareness of risk management and school safety culture. Conclusions: The first aid training program effectively strengthened the competence and confidence of PJOK teachers in responding to sports-related emergencies. Integrating interactive workshops with practical simulations proved to be an effective strategy for improving evidence-based first aid competencies while fostering a sustainable safety culture in schools. The program also contributes to educational management by reinforcing teachers' roles as safety managers and supporting the development of safer physical education practices.